2020
DOI: 10.1021/jacs.0c02188
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Large Isotropic Negative Thermal Expansion in Framework Compound AgB(CN)4 via the Concept of Average Atomic Volume

Abstract: Exploring isotropic negative thermal expansion (NTE) compounds is interesting, but remains challenging. Here, a new concept of "average atomic volume" is proposed to find new NTE open-framework materials. According to this guidance, two NTE compounds, AgB(CN) 4 and CuB(CN) 4 , have been discovered, of which AgB(CN) 4 exhibits a large NTE over a wide temperature range (α v = −40 × 10 −6 K −1 , 100−600 K). The analysis by extended X-ray absorption fine structure spectroscopy and first-principles calculation indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 37 publications
1
96
0
Order By: Relevance
“…Due to their flexible networking architecture, many cyanides/Prussian blue analogues (PBAs), such as Zn(CN) 2 [29], ZnPt(CN) 6 [30], LaCo(CN) 6 [31] and ScCo(CN) 6 [32] , display a fascinating NTE behavior. Gao et al [33] reported the large NTE behavior in YFe(CN) 6 , whose AAV is 22.58 Å 3 , well above the critical point (assessed to ~16 Å 3 by Gao et al [28]). The framework structure of isostructural materials with formula REFe(CN) 6 consists of REN 6 trigonal prisms alternating with FeC 6 octahedra, as shown in Fig.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Due to their flexible networking architecture, many cyanides/Prussian blue analogues (PBAs), such as Zn(CN) 2 [29], ZnPt(CN) 6 [30], LaCo(CN) 6 [31] and ScCo(CN) 6 [32] , display a fascinating NTE behavior. Gao et al [33] reported the large NTE behavior in YFe(CN) 6 , whose AAV is 22.58 Å 3 , well above the critical point (assessed to ~16 Å 3 by Gao et al [28]). The framework structure of isostructural materials with formula REFe(CN) 6 consists of REN 6 trigonal prisms alternating with FeC 6 octahedra, as shown in Fig.…”
mentioning
confidence: 88%
“…Recently, Gao et al [28] proposed a new concept of average atomic volume (AAV) by summarizing the structural characteristics of isotropic framework NTE materials and successfully discovered the NTE material AgB(CN) 4 . The concept of AAV is a simple parameter to indicate the average volume of atoms in a unit cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gao et al suggested a simple rule based on the concept of average atomic volume (AAV) according to the statistical data of NTE materials, where they proposed a critical AAV of 16 Å 3 for the framework compounds with NTE property, and they believed that the flexibility of the structure is the key factor for the NTE characteristics (Gao et al, 2020c). It provides a simple way to search for and discover new NTE materials.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Positive TE (PTE) is the most common behavior in materials 2 , 3 and involves an increase in size upon heating. Alternatively, negative TE (NTE) is rarer 4 6 and corresponds to a decrease in size upon heating. Lastly, near-zero or zero TE materials are quite rare 7 9 and are characterized by minimal to no change in response to temperature.…”
Section: Introductionmentioning
confidence: 99%